Unstained DNA Origami Imaging: Imaging of Unstained DNA Origami Triangles with Electron Microscopy (Small Methods 12/2019). Issue 12 (2nd December 2019) - Londono‐Calderon, Alejandra; Hossen, Md Mir; Palo, Pierre E.; Bendickson, Lee; Vergara, Sandra; Nilsen‐Hamilton, Marit; Hillier, Andrew C.; Prozorov, Tanya
Abstract : In articule number 1900393 by Tanya Prozorov and co‐workers, scanning transmission electron microscopy (EM) is used for direct visualization of key structural elements of a DNA origami triangle with sufficient resolution, without negative staining. One of the advantages of EM analysis of DNA origami is the implementation of analytical spectroscopy techniques.